Review articlePredictive factors of acute coronary syndrome and restenosis - Markuszewski, Leszek; Miczek, Paweł; Tyślerowicz, Piotr; Ruxer, Jan; Pietruszyński, Robert (Przegląd Kardiodiabetologiczny/Cardio-Diabetological Review, 2006)
Coronary artery disease, and especially acute coronary syndromes (ACS), are found to be one of the most important risk factors of disability and mortality. Despite quite good understanding of the pathomechanism of the disease, it is still difficult to determine the direct risk factors leading to ACS. Predicting laboratory factors of ACS are: selected blood morphology parameters, fibrinogen, interleukins, C-reactive protein, adhesion molecules, metalloproteinases and TNF-alpha. These parameters are the result of pathological changes accompanied to metabolic process (for example diabetes) and arterial hypertension and initiate or intensify the inflammatory process, especially with coexisting hypercholesterolaemia. It is determined that among metabolic disturbances especially dyslipidaemia and insulin resistance lead to oxidative stress, activation of kinases, neurohormonal stimulation and endothelium dysfunction, expressed by disturbances of NO synthesis. The most important predictor of cardiovascular events, unrelated to diabetes, is also HbA1c level. According to the multimarker strategy it is important to evaluate the risk factors from various groups that can better define the risk of cardiovascular events. Most of the analyzed parameters, even of recognized prognostic value, cannot be useful in practice because of methodological and economic limitations. Considering these aspects, it seems that only CRP and HbA1C play an important role in clinical settings.